Steroid-refractory PD-(L)1 pneumonitis: incidence, clinical features, treatment, and outcomes. Issue 1 (7th January 2021) - Balaji, Aanika; Hsu, Melinda; Lin, Cheng Ting; Feliciano, Josephine; Marrone, Kristen; Brahmer, Julie R; Forde, Patrick M; Hann, Christine; Zheng, Lei; Lee, Valerie; Illei, Peter B; Danoff, Sonye K; et al.
Abstract : Background: Immune-checkpoint inhibitor (ICI)-pneumonitis that does not improve or resolve with corticosteroids and requires additional immunosuppression is termed steroid-refractory ICI-pneumonitis. Herein, we report the clinical features, management and outcomes for patients treated with intravenous immunoglobulin (IVIG), infliximab, or the combination of IVIG and infliximab for steroid-refractory ICI-pneumonitis. Methods: Patients with steroid-refractory ICI-pneumonitis were identified between January 2011 and January 2020 at a tertiary academic center. ICI-pneumonitis was defined as clinical or radiographic lung inflammation without an alternative diagnosis, confirmed by a multidisciplinary team. Steroid-refractory ICI-pneumonitis was defined as lack of clinical improvement after high-dose corticosteroids for 48 hours, necessitating additional immunosuppression. Serial clinical, radiologic (CT imaging), and functional features (level-of-care, oxygen requirement) were collected preadditional and postadditional immunosuppression. Results: Of 65 patients with ICI-pneumonitis, 18.5% (12/65) had steroid-refractory ICI-pneumonitis. Mean age at diagnosis of ICI-pneumonitis was 66.8 years (range: 35–85), 50% patients were male, and the majority had lung carcinoma (75%). Steroid-refractory ICI-pneumonitis occurred after a mean of 5 ICI doses from PD-(L)1 start (range: 3–12 doses). The most common radiologic pattern was diffuse alveolar damage (DAD: 50%, 6/12). After corticosteroid failure, patients were treated with: IVIG (n=7), infliximab (n=2), or combination IVIG and infliximab (n=3); 11/12 (91.7%) required ICU-level care and 8/12 (75%) died of steroid-refractory ICI-pneumonitis or infectious complications (IVIG alone=3/7, 42.9%; infliximab alone=2/2, 100%; IVIG + infliximab=3/3, 100%). All five patients treated with infliximab (5/5; 100%) died from steroid-refractory ICI-pneumonitis or infectious complications. Mechanical ventilation was required in 53% of patients treated with infliximab alone, 80% of those treated with IVIG + infliximab, and 25.5% of those treated with IVIG alone. Conclusions: Steroid-refractory ICI-pneumonitis constituted 18.5% of referrals for multidisciplinary irAE care. Steroid-refractory ICI-pnuemonitis occurred early in patients' treatment courses, and most commonly exhibited a DAD radiographic pattern. Patients treated with IVIG alone demonstrated an improvement in both level-of-care and oxygenation requirements and had fewer fatalities (43%) from steroid-refractory ICI-pneumonitis when compared to treatment with infliximab (100% mortality).